Cancer Cell Image Segregation - Wong, Hon Choong (Universiti Sains Malaysia, 2006)
Breast cancer is one of the common diseases among women nowadays. Some methods to detect or identify breast cancer including pap smear image testing, mammogram and ultrasound screening, Self Breast Checks, fine needle aspiration (FNA) and other. However, some weakness we face must be solved in order to obtain the accurate data from medical image such as image of breast cancer cells that is overlapping of cell image in cluster will affect the data. A system was build by using Borland C++ Builder through this project to detect the edge of cell image and segregate those overlapping cells image. The implementation of techniques like edge detection and segmentation are used. According to results, most of those techniques are successful to detect edge and do segmentation.